2018
DOI: 10.1016/j.devcel.2018.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Sequestration of a Transposon-Derived siRNA by a Target Mimic Imprinted Gene Induces Postzygotic Reproductive Isolation in Arabidopsis

Abstract: Genomic imprinting is an epigenetic phenomenon occurring in mammals and flowering plants, causing genes to be expressed depending on their parent of origin. In plants, genomic imprinting is mainly confined to the endosperm, a nutritive tissue supporting embryo growth, similar to the placenta in mammals. Here, we show that the paternally expressed imprinted gene PEG2 transcript sequesters the transposable element (TE)-derived small interfering RNA (siRNA) siRNA854 in the endosperm. siRNA854 is present in the ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 45 publications
3
23
0
Order By: Relevance
“…Consistent with our findings, a recent study found that spontaneous retrotransposon mutations are much more frequent through the male than the female in certain maize lines [31]. This conservation suggests that the roles of TE and TE-induced small RNAs during reproductive development may also be conserved between monocots and eudicots [35,56,57].…”
Section: Transposable Element Dynamics In the Maize Male Gametophytesupporting
confidence: 91%
“…Consistent with our findings, a recent study found that spontaneous retrotransposon mutations are much more frequent through the male than the female in certain maize lines [31]. This conservation suggests that the roles of TE and TE-induced small RNAs during reproductive development may also be conserved between monocots and eudicots [35,56,57].…”
Section: Transposable Element Dynamics In the Maize Male Gametophytesupporting
confidence: 91%
“…We failed to obtain a significant increase in viable paternal excess seeds using 4n rdr6-15 pollen ( Figure 1A; Supplemental Figure 1B), suggesting that any sRNAs exclusively dependent on RDR6 are not linked to paternal excess seed abortion. Consistent with this result, paternally produced siR-NA854, which is dependent on DCL2/4 and RDR6, is required for the viability of paternal excess seeds (McCue et al, 2012;Wang et al, 2018). By contrast, we found that multiple members of the canonical RdDM pathway restore paternal excess seed viability (Figure 1; Supplemental Figures 1A and 1C).…”
Section: Impact On Models For Interploidy Seed Abortionsupporting
confidence: 85%
“…The ability of maternal sporophytic mutations in the flavonoid pathway to repress paternal excess seed abortion is consistent with this model (Dilkes et al, 2008;Doughty et al, 2014). The expression levels of AGAMOUS-LIKE genes (AGLs), the small RNA (sRNA) siRNA854, chromatin regulators, cell wall genes, and defense response genes, all presumed to act in the endosperm, have been linked to paternal excess seed abortion (Walia et al, 2009;Burkart-Waco et al, 2013;Kradolfer et al, 2013;Wolff et al, 2015;Jiang et al, 2017;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…This allows STTMs to be used to knock down unrelated miRNAs, belonging to different families. Beyond miRNAs, STTMs have also been successfully used to silence the expression of siRNAs (McCue et al, 2013;Wang et al, 2018).…”
Section: Discussion Sttms Are Valuable Tools For Dominant Knockdown Omentioning
confidence: 99%